Enhancing slope stability with different slope stabilization measures: a case study using SLOPE/W Software - Norhanizah Hamzah,; Rozaini Ramli,; Masyitah Md Nujid,; Siti Fatimah Sadikon, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper presents a case study of an existing slope at Taman Kelab Ukay, Ampang, Selangor. A potential slope failure is predicted as the nearby surrounded slope failed due to low self-retaining strength caused by prolonged and intense rainfall. The slope stability is analyzed by the Limit Equilibrium Method (LEM) using Geo-Studio 2018 (SLOPE/W) software to investigate the slope’s Factor of Safety (FOS). The slope stability analysis confirms that the existing slope only provides the FOS of 1.028, which does not meet the minimum FOS of 1.30 of JKR Guidelines for Slope Design (2010) for untreated slope. The slope is subsequently re-analyzed as a treated slope, and the proposed remedial actions are soil nailing and geotextiles. As a result, the soil nailing and geotextiles achieve a minimum FOS of 1.50 for treated slope, with values of 1.899 and 1.845, respectively. For remedial work, soil nailing is recommended to be employed at the slope since the method is commonly used in the construction industry as it offers an inexpensive and uncomplicated installation technique. The sufficient soil nailing design characteristics proposed for the slope is three (3) bars of 7 meters length of soil nails at a 25° inclination angle. Soil nailing is a reliable and cost-effective method for slope stabilization and remedial work due to its ability to provide a durable, long-term solution for slopes that are prone to instability, erosion and landslides.